2021
DOI: 10.1007/s00394-021-02525-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond protein intake: does dietary fat intake in the year preceding pregnancy and during pregnancy have an impact on gestational diabetes mellitus?

Abstract: Purpose Studies regarding the association between dietary fat intake and gestational diabetes mellitus (GDM) are limited and provide conflicting findings. Thus, the study aims to examine the association of dietary fat intake in the year preceding pregnancy and during pregnancy with the risk of GDM, taking the relevance of dietary protein intake on GDM into consideration. Methods A prospective study was conducted in 6299 singleton pregnancies, using the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…Similar to GDM, T2DM also results from a mixture of insulin resistance and dysfunctional insulin secretion. However, another Chinese pregnant women cohort study (14) elucidated no significant association between total fat intake in the first trimester and GDM risk, which was not consistent with our results. In the former study, dietary information was collected by a food frequency questionnaire, and the main source of fat was animal food; while we gathered dietary information by 3-day dietary recalls, and the fat in our study mainly came from vegetables.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to GDM, T2DM also results from a mixture of insulin resistance and dysfunctional insulin secretion. However, another Chinese pregnant women cohort study (14) elucidated no significant association between total fat intake in the first trimester and GDM risk, which was not consistent with our results. In the former study, dietary information was collected by a food frequency questionnaire, and the main source of fat was animal food; while we gathered dietary information by 3-day dietary recalls, and the fat in our study mainly came from vegetables.…”
Section: Discussioncontrasting
confidence: 99%
“…In this stage, twenty-nine articles were excluded due to the following reasons: irrelevant articles (n � 19), cross-sectional studies (n � 3), case-control studies (n � 4), and studies with insufcient data (n � 3). Six cohort studies were fnally included in the systematic review and meta-analysis [12,[20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding to our results, a sub-study of the Protein Overfeeding trial [ 33 ] examined the changes in blood lipids under over-ingestion of high and low protein diets, elucidating that protein intake and fat intake were inversely related. Moreover, A prospective study [ 34 ] indicated that the association between higher take of dietary fat and gestational diabetes mellitus risk was drastically attenuated after adjustment for animal protein intake. It was not unique but had its counterpart.…”
Section: Discussionmentioning
confidence: 99%